Χρήσεις του προσωνυμίου «Γαλιλαίοι» και του εθνωνύμου «¨Ελλην» στο έργο του Ιουλιανού - ΘΕΟΔΩΡΙΔΗΣ Ιάσων (Byzantina Symmeikta, 2022)
After the first half of the fourth century, the Christian doctrine appeared to be the indisputable, sovereign cult, in the religious conflicts that took place in the vast acreage of Late Roman Empire. Not only it prevailed upon the various pagan cults of the empire, but it also ended up as the imperial cult. Earlier this period, the ethnonym “Hellen” adopted a novice, “religious- based” meaning, designating “pagans”, which would prevail among others in the following centuries. Emperor Julian’s reign (361-363) comprised a brief disruption of the inevitable domination of Christianity. In the present paper, we study the functions of the appellative “Galilean” and the ethnonym “Hellen” in the Julianic corpus, in order to contribute to the apprehension of the Julianic philosophical and religious thought, as well as to illuminate undiscernible shades in the functions of the terms under study